Ocular infections in sub‐Saharan Africa in the context of high HIV prevalence. Issue 9 (7th July 2014) - Schaftenaar, Erik; van Gorp, Eric C. M.; Meenken, Christina; Osterhaus, Albert D. M. E.; Remeijer, Lies; Struthers, Helen E.; McIntyre, James A.; Baarsma, G. Seerp; Verjans, Georges M. G. M.; Peters, Remco P. H.
Abstract Healthy eyes and good vision are important determinants of populations' health across the globe. Sub‐Saharan Africa is affected by simultaneous epidemics of ocular infections and human immunodeficiency virus (HIV). Ocular infection and its complications, along with cataract and ocular trauma, are common conditions in this region with great impact on daily life. In this review, we discuss the epidemiology, clinical manifestations and microbial aetiology of the most important infectious ocular conditions in sub‐Saharan Africa: conjunctivitis, keratitis and uveitis. We focus specifically on the potential association of these infections with HIV infection, including immune recovery uveitis. Finally, challenges and opportunities for clinical management are discussed, and recommendations made to improve care in this neglected but very important clinical field.